Correlating solubility of piperine extraction using empirical models / Siti Nur Aqila Razali - Razali, Siti Nur Aqila (2017)
Bioactive compound, which known as piperine was extracted from Malabar black pepper at temperature of 313, 323 and 333 K and operating pressure of 200, 250 and 300 bar in supercritical carbon dioxide (SCCO2). The experimental data was obtained from literature to be analyzed by using Microsoft Excel 2013 software with the application of four empirical correlation models which are Chrastil’s model (CH), Del Valle and Aguilera’s model (DVA), Kumar and Johnston model (K-J) and Sung and Shim model (S-S) to estimate the solubility data. The comparison of the data was discussed, from the correlated results, the AARD (%) values of CH, DVA, K-J and S-S are 6.9928%, 6.9897 %, 5.7786 % and 5.6075 % with SD of 2.448, 2.447, 2.023 and 1.963. Based on the results obtained, S-S model performed better among the four models and proved the effect of temperature and pressure on the solubility of piperine in SCCO2 with the minimum AARD (%) value that indicates the satisfactory correlation results which have been achieved for each empirical models which has the highest number of parameters present and containing temperature effects, thus, increased the accuracy of the correlation models was employed to predict the solubility of piperine in SCCO2. The thermodynamic properties, total enthalpy, ΔH of the solid solute was obtained which was equivalent to -2867.27 J/mol and can be applied in designing extractor and comparison between SCFs based on diffusion rate of piperine.